Advances in energy system optimization: proceedings of the first International Symposium on Energy System Optimization - Bertsch, Valentin; Fichtner, Wolf; Heuveline, Vincent; Leibfried, Thomas (Birkhäuser, 2017)
1. A Customized Evolutionary Algorithm for the Optimization of Residential Energy Resources -- 2. Comparison of control strategies for electric vehicles on a low voltage level electrical distribution grid -- 3. Optimal Storage Operation with Model Predictive Control in the German Transmission Grid -- 4. Security-Constrained Optimization Framework for Large-Scale Power Systems Including Post-Contingency Remedial Actions and Inter-Temporal Constraints -- 5. Dynamic Decision Making in Energy Systems with Storage and Renewable Energy Sources -- 6. Dispatch of flexibility options, grid infrastructure and integration of renewable energies within a decentralized electricity system -- 7. An Optimal Investment Model for Battery Energy Storage Systems in Isolated Microgrids -- 8. A dynamic programming approach to multi-period planning of isolated microgrids -- 9. Curtailing renewable feed-in peaks and its impact on power grid extensions in Germany for the year 2030 -- 10. Simulation of distribution grid expansion costs and the impact of load shifting -- 11. Structure Analysis of the German Transmission Network using the Open Source Model SciGRID -- 12. Modeling of the transmission grid using geo allocation and generalized processes -- 13. Regionalizing Input Data for Generation and Transmission Expansion Planning Models -- 14. Convexity/nonconvexity certificates for power flow analysis -- 15. A Convex Model for the Optimization of Distribution Systems with Distributed Generation.-
Keywords: Konferenzschrift